Economic Valuation and Ecological Thresholds in the Mangrove-Shrimp System - Kartini Kartini; Patta Tope; Suparman Suparman (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
The conversion of mangrove forests into vannamei shrimp ponds has increased aquaculture production, but at the same time triggered the degradation of coastal ecosystems and the loss of environmental services of high economic value. This study aims to analyze the trade-off between economic benefits and ecological sustainability through estimating Total Economic Value (TEV), testing the effect of pond intensity on mangrove health, and identifying ecological thresholds as the basis for sustainable coastal management. The research uses a mixed-methods approach with a sequential explanatory (QUAN→QUAL) design. Quantitative data were obtained from a survey of 212 farmers, analysis of Landsat/Sentinel imagery for the 2020–2024 period, and then deepened through interviews and Focus Group Discussions (FGD). The analysis was conducted using Ordinary Least Squares (OLS) with Robust Standard Errors, as well as Cost–Benefit Analysis (CBA) and Net Present Value (NPV) evaluations. The results of the study show that the TEV of the mangrove ecosystem reaches Rp306.8 million/ha/year, with Indirect Use Value dominating at 71.2%. The intensity of ponds had a negative and significant effect on the NDVI index (β = –0.710; p < 0.001), while the application of silvofishery had a positive effect on mangrove health. Scenario simulation shows that the silvofishery system with a composition of 60% mangroves and 40% ponds produces the highest economic feasibility (NPV of Rp89.7 million/ha; BCR 2.38) while maintaining ecological function. These findings confirm that the integration of economic valuation and ecological thresholds is an important basis for the formulation of coastal management policies that are able to balance aquaculture productivity and mangrove conservation.